Activation of Nrf2-antioxidant signaling attenuates NF-κB-inflammatory response and elicits apoptosis - Li, Wenge (2008)
Oxidative stress has been implicated in the etiology of neurodegenerative disease, cancer and aging. Indeed, the reactive oxygen and nitrogen species generated by inflammatory cells that created oxidative stress is thought to be one of the major factor by which chronic inflammation contributes to neoplastic transformation as well as many other diseases. We have recently reported that mice lacking nuclear factor-erythroid 2-related factor 2 (Nrf2) are more susceptibility to dextran sulfate sodium (DSS)-induced colitis and colorectal carcinogenesis. Nrf2 is a basic leucine zipper redox-sensitive transcriptional factor that plays a center role in ARE (antioxidant response element)-mediated induction of phase II detoxifying and antioxidant enzymes. We found that increased susceptibility of Nrf2 deficient mice to DSS-induced colitis and colorectal cancer was associated with decreased expression of antioxidant/phase II detoxifying enzymes in parallel with upregulation of pro-inflammatory cytokines/biomarkers. These findings suggest that Nrf2 may play an important role in defense against oxidative stress possibly by activation of cellular antioxidant machinery as well as suppression of pro-inflammatory signaling pathways. In addition, in vivo and in vitro data generated from our laboratory suggest that many dietary compounds can differentially regulate Nrf2-mediated antioxidant/anti-inflammatory signaling pathways as the first line defense or induce apoptosis once the cells have been damaged. In this review, we will summarize our thoughts on the potential cross-talks between Nrf2 and NF-κB pathways. Although the mechanisms involved in the cross-talk between these signaling pathways are still illusive, targeting Nrf2-antioxidative stress signaling is an ideal strategy to prevent or treat oxidative-stress related diseases.